Effects of elevated ozone concentration on CH4 and N2O emission from paddy soil under fully open‐air field conditions - Tang, Haoye; Liu, Gang; Zhu, Jianguo; Kobayashi, Kazuhiko (Global Change Biology, 2015)
We investigated the effects of elevated ozone concentration (E‐O₃) on CH₄and N₂O emission from paddies with two rice cultivars: an inbred Indica cultivar Yangdao 6 (YD6) and a hybrid one II‐you 084 (IIY084), under fully open‐air field conditions in China. A mean 26.7% enhancement of ozone concentration above the ambient level (A‐O₃) significantly reduced CH₄emission at tillering and flowering stages leading to a reduction of seasonal integral CH₄emission by 29.6% on average across the two cultivars. The reduced CH₄emission is associated with O₃‐induced reduction in the whole‐plant biomass (−13.2%), root biomass (−34.7%), and maximum tiller number (−10.3%), all of which curbed the carbon supply for belowground CH₄production and its release from submerged soil to atmosphere. Although no significant difference was detected between the cultivars in the CH₄emission response to E‐O₃, a larger decrease in CH₄emission with IIY084 (−33.2%) than that with YD6 (−7.0%) was observed at tillering stage, which may be due to the larger reduction in tiller number in IIY084 by E‐O₃. Additionally, E‐O₃reduced seasonal mean NOₓflux by 5.7% and 11.8% with IIY084 and YD6, respectively, but the effects were not significant statistically. We found that the relative response of CH₄emission to E‐O₃was not significantly different from those reported in open‐top chamber experiments. This study has thus confirmed that increasing ozone concentration would mitigate the global warming potential of CH₄and suggested consideration of the feedback mechanism between ozone and its precursor emission into the projection of future ozone effects on terrestrial ecosystem.